Exploring in vitro modeling in hepatocarcinogenesis research: morphological and molecular features and similarities to the corresponding human disease - Valente, Leticia Cardoso [UNESP]; Bacil, Gabriel Prata [UNESP]; Riechelmann-Casarin, Luana [UNESP]; Barbosa, Giullia Cavichiolli [UNESP]; Barbisan, Luís Fernando [UNESP]; Romualdo, Guilherme Ribeiro [UNESP] (Elsevier, 2024)
The hepatocellular carcinoma (HCC) features a remarkable epidemiological burden, ranking as the third most lethal cancer worldwide. As the HCC-related molecular and cellular complexity unfolds as the disease progresses, the use of a myriad of in vitro models available is mandatory in translational preclinical research setups. In this review paper, we will compile cutting-edge information on the in vitro bioassays for HCC research, (A) emphasizing their morphological and molecular parallels with human HCC; (B) delineating the advantages and limitations of their application; and (C) offering perspectives on their prospective applications. While bidimensional (2D) (co) culture setups provide a rapid low-cost strategy for metabolism and drug screening investigations, tridimensional (3D) (co) culture bioassays - including patient-derived protocols as organoids and precision cut slices - surpass some of the 2D strategies limitations, mimicking the complex microarchitecture and cellular and non-cellular microenvironment observed in human HCC. 3D models have become invaluable tools to unveil HCC pathophysiology and targeted therapy. In both setups, the recapitulation of HCC in different etiologies/backgrounds (i.e., viral, fibrosis, and fatty liver) may be considered as a fundamental guide for obtaining translational findings. Therefore, a “multimodel” approach – encompassing the advantages of different in vitro bioassays - is encouraged to circumvent “model-biased” outcomes in preclinical HCC research.
Keywords: Cell culture; Hepatocarcinogenesis; Hepatocellular carcinoma; In vitro; Liver cancer; Organoids; Precision cut slices; Spheroids